Unveiling Flaws in Test Identification Parades: A Guide for Reliable Identifications - Maqsood, Burhan; Sarwar, Muhammad Waqas; Azeem, Hafiz Muhammad (Annals of Human and Social Sciences, 2024)
Test Identification Parades (TIPs) play a vital role in criminal cases where witnesses are unacquainted with the offender. Although some directives exist in the Punjab Police Rules, 1934, and Lahore High Court Rules and Orders, Volume III, for the procedure of TIP, yet there is no independent legislation available on it. Many common errors occur during TIPs. This paper aims to highlight those common errors and to offer a practical guide containing guidelines and recommendations to comprehend the procedure of TIP. This study primarily employs analytical legal research methodology. Through an analysis of 20 TIP-related cases, 20 common errors were found. This research concludes that a lack of awareness about TIP procedures hinders successful trials. It recommends independent and joint training programs for all involved in TIP. This study also provides comprehensive recommendations for conducting error-free TIPs.